Urgensi Pembangunan Ma’had Al-Jami’ah dalam Penyelenggaraan Pendidikan Berbasis Pesantren (Studi di UIN K.H. Abdurrahman Wahid Pekalongan) - Ghozani, Sobi (JURNAL ILMIAH GEMA PERENCANA, 2023)
This article describes the issue of implementation of Islamic boarding school -based education that needs to be supported by adequate facilities and infrastructure, one of which is the student dormitory building of UIN K.H. Abdurrahman Wahid Pekalongan, as the only State Islamic Religious College in the former residency of Pekalongan. This article aims to analyze the urgency of the Ma’had Al-Jami’ah student dormitory development program for the implementation of Islamic boarding school-based education at UIN K.H. Abdurrahman Wahid Pekalongan and to examine various opportunities to realize this based on existing conditions. This article uses a qualitative research method, with a descriptive exploratory approach. Data were obtained from various literary sources that are considered credible and from Ma’had Al-Jami’ah UIN K.H. Abdurrahman Wahid Pekalongan related to the student dormitory development program. Then to analyze the data that has been collected, the authors use content analysis techniques. Based on the study conducted, it was found that the student dormitory building at the State Islamic Religious College has two main functions. First, as a proper place to live for students. Second, as a place for Islamic boarding school-based education in higher education by Ma’had Al-Jami’ah. The aims, objectives and benefits of building the Ma’had Al-Jami’ah student dormitory are very important and strategic for UIN K.H. Abdurrahman Wahid Pekalongan as mapped by Ma’had Al-Jami’ah in the 2022 Ma’had Al Jami’ah Special Dormitory Development Proposal. The most visible obstacle at this time is more on the budget side to fund this strategic project.